Toxicity of Copper (11) Tetraoxo Sulphate to African Catfish (Clarias Gariepinus) Fingerlings - F. O , Agbebi; O, Owoeye (Asian Journal of Agriculture and Rural Development, 2012)
This study was carried out to determine the toxicity of copper sulphate to African Catfish (Clarias gariepinus). The range – finding test was conducted twice in order to get reliable values that could be used for the definitive test. The toxicant (copper sulphate) was introduced at varying concentrations of 10g/l, 20g/l, 30g/l and 40g/l in the first range- finding test, while it was introduced at concentrations of 2g/l, 4g/l, 6g/l and 8g/l in the second range- finding test. However, in the definitive test, the toxicant was introduced at varying concentrations of 0.1g/l, 0.125g/l, 0.15g/l, and 0.175g/l. From the definitive test, the Median Lethal Concentration of copper sulphate to Clarias gariepinus was found to be 0.175g/l. The study showed that Clarias gariepinus fingerling exhibited initial erratic movement, rapid opercular movement, skin discoloration and loss of reflex. Also, histopathological alterations such as the degeneration of gill and liver tissues were observed in the fish that were exposed to the toxicant. The water quality data were analyzed by subjecting them to one – way Analysis of Variance (ANOVA).Thus, the study indicates that copper sulphate is toxic to Clarias gariepinus fingerlings.